Developing future-ready learners for a global age : pedagogical innovations in Singapore - Choo, Suzanne S.; Liu, Woon Chia; Chua, Bee Leng (Learning officer) (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Choo, Liu, and Chua offer a dynamic look into the tripartite relationship between education research, policy, and practice that characterizes Singapore's changing education landscape. Over the years, Singapore has garnered increasing attention internationally for its world-class education system. Pushing back against the stereotypical notions of exam- and teacher-centric education in Asia, the contributors to this volume discuss opportunities as well as challenges in Singapore's innovation towards constructivist, critical, culturally responsive and cosmopolitan forms of learning. Highlighting the pedagogical innovation and its context in Singapore's teacher education and schools, the authors bridge theory and practice by providing an understanding of innovative practices informed by key shifts in Singapore's education policies and key conceptual principles informing these practices. More importantly, it provides on-the-ground empirical insights into the ways these innovative pedagogical practices are enacted in the classroom and in teacher education programmes. Each chapter provides in-depth understanding of how these pedagogies are applied across various subject disciplines including guided problem-solving in Mathematics, games-based pedagogy in science, multimodal literacies in language, ethical criticism in Literature, non-linear pedagogy in Physical Education, multicultural approaches in music, among others. Balancing theoretical and empirical focus, this resourceful text will be of interest to students, researchers and practitioners in educational development, pedagogy and teacher education, as well as policymakers across international fields in education"--
Keywords: Critical pedagogy -- Singapore; Education -- Aims and objectives -- Singapore; Problem solving -- Study and teaching -- Singapore; Educational games -- Singapore; Modality (Linguistics) -- Study and teaching -- Singapore; Educational innovations -- Singapore; EDUCATION / Multicultural Education; EDUCATION / Educational Policy & Reform / General; EDUCATION / General